0438 Upper Airway Anatomical Differences between Chinese and Caucasian Patients with Obstructive Sleep Apnea. (12th April 2019) - Xu, Liyue; Keenan, Brendan T; Wiemken, Andrew; Staley, Bethany; Chi, Luqi; Pack, Allan I; Gislason, Thorarinn; Schwab, Richard J
Abstract: Introduction: This study aimed to evaluate upper airway soft tissues and craniofacial structures differences between Chinese and Caucasian patients with obstructive sleep apnea (OSA). Methods: Airway sizes, soft tissue volumes and craniofacial dimensions quantified using three-dimensional magnetic resonance imaging (MRI) were compared between Caucasians (N=134) and Chinese (N=67) patients with moderate-severe OSA (AHI≥15 events/hour) matched for age and gender. Analyses were performed using mixed effects models. Results: When compared to Caucasian patients, Chinese OSA patients had similar age (49.61±9.78 vs. 49.62±9.72 years, p=0.8702), lower BMI (28.0±3.5 vs. 33.46±5.67 kg/m 2, p<0.0001) and no significant difference in AHI (45.68±21.54 vs. 41.3±15.78 events/hour, p=0.0959) ; smaller RP airway mean cross-sectional area (80.78±37.82 vs 147.3±62.8 mm 2, p<0.0001 ) which may be contributed by bigger soft palate (11240±3422 vs 9801±2267 mm 3, p<0.0001), but smaller combined soft tissues (176849±27366 vs 205000±33818 mm 3, p<0.0001 ); bigger ANB angle (5.26±3.13 vs 2.93±2.66°, p<0.0001), different shaped mandibular including shorter mandibular corpus length (78.56±4.82 vs 94.41±6.60 mm, p<0.0001) but longer mandibular ramus length (66.40±5.75 vs 45.36±6.51mm, p<0.0001), and wider (width first molar 48.7±2.79vs 45.21±3.02 mm, p<0.0001) and shallower (unit depth 44.47±4.11 vs 47.57±3.96 mm, p<0.0001) maxillary. These findings remained after controlling age, AHI, height or age, AHI, BMI. Conclusion: When compared to Caucasian patients, Chinese patients had bigger soft palates which likely contributes to the smaller airway in the retropalatal region, smaller combined soft tissue, and different shaped mandibular and maxillary bones. The anatomical basis of OSA is different in Caucasians and Chinese in several ways. Support (If Any): LX was supported by Young Elite Scientists Sponsorship Program of China Association for Science and Technology. Funds were also provided by NIH grant P01 HL094307.